Instagram Social Media As Guidance And Counseling Media Based On Technology - Noviyanti, Nur Irma (International Journal of Applied Guidance and Counseling, 2020)
one of the most important counselor tasks to response industrial revolution 4.0 is guidance and counselingservice using new innovation, suchus social-media. Internet user Indonesia are 64,8 % from all citizen, with user duration using social-media 3-4 hours each day. Social media acess is the second priority after using communication needed. Instagram is the second social-media with high access by user after facebook. Instagram is one of social-media application to share text, image, or video.Â  This work is gained to analyse that instagram could be used by counselor as media to do guidance and counseling service based on technology.Â  There are many fiture such us image upload, video, caption, comment, hashtags, instagram story, instagram live, direct message and highlight could be used by counselor.